Infection and pathological lesions of lymph nodes induced by Linguatula serrata nymphs in one-humped camels in Iran - TAVASSOLI, M.; HOBBENAGHI, R.; KARGOZARI, A.; REZAEIA, H. (Journal of the Hellenic Veterinary Medical Society, 2018)
Linguatula serrata (Pentastomida: Linguatulidae) known tong-worm is a cosmopolitan, zoonotic, and obligate endoparasite. The parasite lives in the nasopharyngeal region of the final hosts, which primarily include dogs and other carnivores. Various herbivores, including, camels serve as the best intermediate hosts for nymph stages. In present study the mesenteric lymph nodes of 101camels were examined for infection to L. serrata macroscopically and histopathologically. The infected and normal lymph nodes were processed for histopathology. The results indicated that out of 101 sampled 33 (32.67%) were infected. Macroscopic examination revealed that the infected lymph nodes are swollen and dark, with rubbery consistency, some with subcapsular hemorrhage on cutting. Extensive hemorrhage occurred in various parts of infected lymph nodes. A section of L. serrata parasite was observed near one of the hemorrhage centers. Neutrophil count was very high in these centers and giant cells were present around the parasite, indicating granulomatous reaction. Our findings confirmed that different regions of Iran is an endemic for L. serrata infections. Because L. serrata is a zoonotic parasite, preventive measures should be adopted to disrupt the parasite’s life cycle and minimize the risk of infection in both humans and other animals.